Aligning policy and legal frameworks for supporting smallholder farming through public food procurement: The case of home-grown school feeding programmes - Luana F. Joppert Swensson (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
In the past few years, various countries, regions and cities from low-income to high-income economies have been developing a range of food procurement initiatives designed to use the regular demand for food on the part of government entities as a policy instrument targeting broader development objectives. These initiatives - also referred to as Institutional Food Procurement Programmes (IFPPs)3 - are based on the premise that public institutions, when using their financial capacity and purchasing power to award contracts, can go beyond the immediate scope of responding to the state's procurement needs by addressing additional social, environmental or economic needs that contribute to the overall public good of the state (McCrudden 2004; De Schutter 2014; Kelly and Swensson 2017). In particular, public food procurement initiatives have been recognised, especially in low-income economies, as a potential policy instrument to support local and smallholder farmers and to help integrate them into markets. They are thus recognised as a potential driver of the transformative development of local food systems (Morgan and Sonnino 2008; Sumberg and Sabates-Wheeler 2010; Gelli and Lesley 2010; Foodlinks 2013; De Schutter 2014; 2015; Fitch and Santo 2016; HLPE 2017; Kelly and Swensson 2017; UNSCN 2017).
Keywords: 330; Aligning; policy; legal; framework; supporting; smallholder; farming; through; public; food; procurement; case; home-grown; school; feeding; programmes